(untitled) (Bulletin KNOB, 2008)
The round St. Nicolas Chapel on the Valkhof in the city of Nijmegen is one of the oldest buildings in the Netherlands. Since the beginning of the 19th century the building has been subject to research and discussion. The current research project has shown that the chapel was originally built before the demolition of the Valkhof in the year 1047. Mortar analysis has clearly provided the division between the parts dating from the 11th and 12th centuries. Elements like the joints, cubical capitals, groined vaults and wall structure indicate that the first chapel was built around the year 1030, probably in commission of Emperor Conrad II. It was not until the second half of the 12th century that Frederick Barbarossa decided to rebuild the Valkhof. The chapel was reconstructed in its old form, with only slight alterations. Due to an unknown demolition, the chapel was partly rebuilt for the second time at the end of the 14th century. Dendrochronological research provided the years 1393 and 1394, which dates could be sustained by written sources. Although the second rebuilding of the chapel constitutes the most historic building substance of the chapel, the original outline of the 11th century building is still recognisable nowadays.